The Odesa Image in Odesa-Themed Restaurants - Dovgopolova, Oksana (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2022)
The popularity of Odesa-themed restaurants across the world presents an opportunity to explore a possible core of the Odesa city myth, sedimented into consumer space. The article analyzes 63 enterprises in seventeen countries, examining the cuisine, interiors, restaurant concepts, media reviews, and visitor reports on social media. The theoretical framework of this study revolves around the concept of memory entrepreneurship, the concept of travelling mnemonic plots, and instruments of marketing semiotics, especially the “cultural mélange” phenomenon. The surveyed restaurants reveal a specific picture of an Odesa “memoryscape,” formed as a dense palimpsest. The key themes are the motifs of an inverted world and of a lost Paradise. The plot of the Odesa myth in restaurants outside Odesa can be described as a temporal loop, starting at several points simultaneously, traversing the space of the world, then collapsing and returning to the departure time in a gesture of grief over the lost paradise.